The dual role of p63 in cancer - Xu, Yongfeng; Yang, Xiaojuan; Xiong, Qunli; Han, Junhong; Zhu, Qing (Frontiers in Oncology, 2023)
The p53 family is made up of three transcription factors: p53, p63, and p73. These proteins are well-known regulators of cell function and play a crucial role in controlling various processes related to cancer progression, including cell division, proliferation, genomic stability, cell cycle arrest, senescence, and apoptosis. In response to extra- or intracellular stress or oncogenic stimulation, all members of the p53 family are mutated in structure or altered in expression levels to affect the signaling network, coordinating many other pivotal cellular processes. P63 exists as two main isoforms (TAp63 and ΔNp63) that have been contrastingly discovered; the TA and ΔN isoforms exhibit distinguished properties by promoting or inhibiting cancer progression. As such, p63 isoforms comprise a fully mysterious and challenging regulatory pathway. Recent studies have revealed the intricate role of p63 in regulating the DNA damage response (DDR) and its impact on diverse cellular processes. In this review, we will highlight the significance of how p63 isoforms respond to DNA damage and cancer stem cells, as well as the dual role of TAp63 and ΔNp63 in cancer.